(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Disruptive business environment such as the Covid-19 pandemic and the recent high volatility in commodity prices has changed the way businesses were conducted. The heavy equipment industry is one of many industries affected by such a disruptive environment, especially those who are related to the mining industry where the volatility of the commodity prices has a significant impact on their business performance. Alliances are commonly formed by heavy equipment distributors and their customers to create a mutual benefit to sustain their performance. Strategic alliances have attracted substantial attention from industry as well as academia as a way to stay competitive. Most strategic alliances focus on the strategic alliances partner-to-partner in serving their customers. Consumer behaviour has changed due to disruptive forces that make firms’ strategic focus more on human-centric business approaches. This study looks at the roles of strategic alliances in the partner-to-customer relationship, innovation capability, and cost reduction toward customer loyalty and competitive advantage. Data was collected from 335 respondents from the firms that have entered into strategic alliances. This study finds strategic alliances have the highest association with cost reduction, followed by their association with innovation capability. Strategic alliances enhance customer loyalty through innovation capability. Cost reduction is not a lever to develop customer loyalty in the strategic alliance partner-to-customer relationship. The study also confirms that operational efficiencies are necessarily the source of competitive advantage, but strategic alliances are.